Aspek-Aspek Arsitektur Kolonial Belanda Pada Bangunan Pendopo Puri Mangkunegaran Surakarta - S Samsudi; Agung Kumoro W; Dyah Susilowati Pradnya Paramita; Anita Dianingrum (ARSITEKTURA, 2020)
Dutch colonial architecture that developed in Indonesia, throughout the colonial period (around the 17th century to 1942) was a combination of colonial and local culture to respond to the Indonesian climate. Dutch colonial architecture in Indonesia is a work of Dutch colonial heritage in Indonesia during the colonial period. The result was the Dutch East Indies style with a "colonial" image and adapted to the local environment that responded to climate. Colonial architecture grafted architecture from European countries into colonies. The aspects of Dutch colonial architecture in the "Pendopo Puri Mangkunegran" building were studied to find out the elements of Dutch colonial architecture. "Pendopo Puri Mangkunegarn" is a vernacular architecture / Javanese architecture with a pillar structure system, allegedly there is an architectural element from the outside due to acculturation. The results of this study will be encouraged to know aspects of Dutch colonial architecture in the "Pendopo Puri Mangkunegaran" building from aspects of floor plans, structures, materials and other architectural elements. The results of this study are also expected to contribute knowledge in the field of architecture related to acculturation of foreign cultures that have an impact on local architecture.